NANOTECHNOLOGY-BASED THERAPIES IN THE TREATMENT OF TYPE 2 DIABETES: A NARRATIVE REVIEW - Jagoda Józefczyk; Paweł Buć; Karolina Buć; Łukasz Krzystek; Konrad Zieliński; Karolina Ganczar; Michał Mazurek; Marianna Rudzińska; Mikołaj Zalewski; Stanisław Jurkowski (International Journal of Innovative Technologies in Social Science, 2025)
Type 2 diabetes mellitus (T2DM) remains a major global health burden, driven by insulin resistance, progressive β-cell dysfunction, chronic inflammation, and metabolic dysregulation. Conventional pharmacotherapies often exhibit limited bioavailability, suboptimal targeting, and insufficient capacity to modulate the underlying mechanisms of disease progression. In recent years, nanotechnology has emerged as a highly promising therapeutic strategy capable of addressing these limitations. This narrative review evaluates current advancements in nanotechnology-based interventions for T2DM, with a focus on nanocarrier design, mechanisms of action, and translational potential. Across the analyzed studies, diverse nanoplatforms—including polymeric nanoparticles, lipid-based nanocarriers, nanomicelles, PLGA systems, bilosomes, gold nanoparticles, and stimulus-responsive Pickering emulsions—demonstrated significant improvements in drug stability, controlled release, intestinal absorption, and metabolic outcomes. Notably, nanocarriers enhanced the therapeutic performance of incretin-based agents (GLP-1, liraglutide), enabled progress toward oral insulin delivery, and increased the bioavailability of conventional antidiabetic drugs such as metformin and glimepiride. Additionally, nanostructures encapsulating natural bioactive compounds (e.g., naringenin, oleanolic acid, resveratrol) exhibited potent antioxidant, anti-inflammatory, and metabolic benefits. Several innovative systems further demonstrated glucose- or pH-responsive behavior, enabling intelligent and targeted drug release. Preclinical evidence consistently showed improved glycemic control, enhanced β-cell protection, reduced inflammatory markers, and favorable effects on lipid metabolism and body weight. However, the predominance of in vitro and in vivo animal studies underscores the need for robust clinical investigations to evaluate long-term safety, pharmacokinetics, and real-world therapeutic efficacy. Overall, nanotechnology offers a promising avenue for the development of more effective, precise, and multidimensional treatments for T2DM. Continued translational and clinical research is essential to support its integration into future diabetes management.